Fujiwara no Akihira and Shin Sarugakuki: Kanbun, Heian scholars, and social criticism - Tu, L (2020)
Kanbun 漢文 (literally, Chinese-style writing) is a Japanese writing system that grew out of the adoption and adaptation of Classical Chinese and flourished in the Nara period (710–794). Prior to the advent of modern Japanese writing, kanbun was used to compose many original texts of Japanese literature, as well as being used for reference books and official documents. This dissertation explores a particular work of kanbun of the Heian period — Shin Sarugakuki 新猿楽記 (The Account of New Monkey Music), written by Fujiwara no Akihira 藤原明衡 (989–1066). In terms of both content and writing style, this text has some unconventional, even risqué, aspects that challenge traditional understandings of Heian kanbun, which were more typically focused on government, scholarship, and the public sphere. Shin Sarugakuki offers a different lens through which to view Heian literati and their approach to self-expression, social criticism, and the relationship between commoners and elites.